Partnerships for skill development in Russia. Issue 1 (2nd January 2020) - Remington, Thomas F.; Marques, Israel
ABSTRACT: What conditions enable governments, educational institutions, and enterprises to organise joint, comprehensive technical and vocational education systems (TVET) in developing and transitional countries? This paper explores this question on the basis of an original survey of enterprises in 12 Russian regions designed to determine the factors affecting local adoption of German-style 'dual education' in TVET. We distinguish between firm-level and regional-level factors influencing firms to form institutionally costly partnerships with vocational schools and government entities for the sake of upgrading skill formation. Our findings point to the importance of state intervention in fostering and enforcing firm-school partnerships in settings lacking the dense network of labor and business organizations characteristic of coordinated market economies in Western Europe.